2022
DOI: 10.3390/biom12070893
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological Approaches to Optimize the Production of Amaryllidaceae Alkaloids

Abstract: Amaryllidaceae alkaloids (AAs) are plant specialized metabolites with therapeutic properties exclusively produced by the Amaryllidaceae plant family. The two most studied representatives of the family are galanthamine, an acetylcholinesterase inhibitor used as a treatment of Alzheimer’s disease, and lycorine, displaying potent in vitro and in vivo cytotoxic and antiviral properties. Unfortunately, the variable level of AAs’ production in planta restricts most of the pharmaceutical applications. Several biotech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“… 32 Anthocyanin biosynthesis (ko00942) was the most significantly enriched pathway in Figure 7 B (p value = 0.00), in which kaempferol 3-sophorotropioside (C12635), pelargonidin-5-glucoside-3-sambubioside (C20492), malonylshisonin (C16299), and albireodelphin (C16354), which are biological flavonoids, have the ability to scavenge free radicals and provide antioxidation functions. 33 Isoquinoline alkaloid is a plant alkaloid derived from tyrosine metabolism (ko00350, p value = 0.01), which is involved in various biological activities. 34 N-methylnicotinate (C01004) and dihydroxy-methylcanadine (C21587) are examples of isoquinoline skeleton components upregulated in strain LG3145, 35 , 36 which also possess strong pharmacological and antibacterial properties ( Datas S15 and S16 ).…”
Section: Resultsmentioning
confidence: 99%
“… 32 Anthocyanin biosynthesis (ko00942) was the most significantly enriched pathway in Figure 7 B (p value = 0.00), in which kaempferol 3-sophorotropioside (C12635), pelargonidin-5-glucoside-3-sambubioside (C20492), malonylshisonin (C16299), and albireodelphin (C16354), which are biological flavonoids, have the ability to scavenge free radicals and provide antioxidation functions. 33 Isoquinoline alkaloid is a plant alkaloid derived from tyrosine metabolism (ko00350, p value = 0.01), which is involved in various biological activities. 34 N-methylnicotinate (C01004) and dihydroxy-methylcanadine (C21587) are examples of isoquinoline skeleton components upregulated in strain LG3145, 35 , 36 which also possess strong pharmacological and antibacterial properties ( Datas S15 and S16 ).…”
Section: Resultsmentioning
confidence: 99%
“…The leaf number and average length were 1.95 and 9.38 cm, respectively, and for the root, 4.86 and Recent studies with Amaryllidaceae species have shown that propagation methods [9] and the plant habitat [10] can alter phytochemistry, varying the abundance of secondary metabolites for the same species. Many in vitro propagation studies evaluated the influence of culture medium composition on the seedling phytochemistry and opted to vary the type and concentration of the carbohydrate source, with sucrose being the most common [11,12]. According to the literature [13], increasing the concentration of sucrose in the culture medium up to 90 gL −1 increases the biomass of some Amaryllidaceae species.…”
Section: Vegetative Growth In a Greenhousementioning
confidence: 99%
“…These studies are important to increase biomass production, improve yields and the relative abundance of target compounds [ 12 ]. Furthermore, evaluating vegetative growth and determining the localization of these compounds in plant tissues can provide a better understanding of the role and sites of synthesis and accumulation of these compounds [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…GAL is derived from the extract of Amaryllidaceae plants which produce a series of unique isoquinoline alkaloids with relevant pharmacological properties [31][32][33][34][35][36]. So far, the exact mechanism by which GAL exerts its pharmacological activity is not fully understood: GAL has been proposed as a reversible, competitive and selective AChE inhibitor, and as a ligand of the nicotinic acetylcholine receptors leading to an increase in neurotransmitters secretion [37].…”
Section: Introductionmentioning
confidence: 99%